On a property of the generalized Brauer pairs - COCONEȚ, Tiberiu (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
In this paper we give a generalization of a result of Puig and Zhou to the context of group graded algebras. We use this generalization for an alternative approach of the proof of a result involving group graded basic Morita equivalences. Mathematics Subject Classification (2010): 20C20, 20C05.